2017
DOI: 10.1016/j.plefa.2017.03.001
|View full text |Cite
|
Sign up to set email alerts
|

Comparative effects of high oleic acid vs high mixed saturated fatty acid obesogenic diets upon PUFA metabolism in mice

Abstract: Emerging evidence indicates that the fatty acid composition of obesogenic diets influences physiologic outcomes. There are scant data regarding how the content of non-essential fatty acids like monounsaturated fatty acids (MUFA) and saturated fatty acids (SFAs) impact the metabolism of polyunsaturated fatty acids (PUFAs). In this work, we tested the hypothesis that obesogenic diets enriched in oleic acid (OA; 18:1n-9) reduce polyunsaturated fatty acid (PUFA) levels vs an obesogenic diet enriched in SFAs. Adult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
18
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(25 citation statements)
references
References 58 publications
7
18
0
Order By: Relevance
“…However, to our knowledge, this is the first report demonstrating that feeding laying hens an oil rich in OLA attenuates the deposition into egg yolk of ALA from supplemental FLAX, as well as hepatically synthesized VLC n-3 PUFA derivatives of ALA. Moreover, this finding supports recent reports in mice, where a high monounsaturated fatty acid (MUFA) diet markedly reduced the hepatic contents of ALA and its VLC n-3 PUFA derivatives (except for DHA) in several tissues (Picklo, Idso, Seeger, Aukema, & Murphy, 2017;Picklo & Murphy, 2016). In the present study, egg DHA contents were greatly increased by FLAX feeding (maximum of 106 mg/egg with the 20 g FLAX/kg diet vs. 36 mg/egg with 0 supplemental FLAX) and maximally decreased by~9% at each level of supplemental HOSO (see legend of Fig.…”
Section: Discussionsupporting
confidence: 91%
“…However, to our knowledge, this is the first report demonstrating that feeding laying hens an oil rich in OLA attenuates the deposition into egg yolk of ALA from supplemental FLAX, as well as hepatically synthesized VLC n-3 PUFA derivatives of ALA. Moreover, this finding supports recent reports in mice, where a high monounsaturated fatty acid (MUFA) diet markedly reduced the hepatic contents of ALA and its VLC n-3 PUFA derivatives (except for DHA) in several tissues (Picklo, Idso, Seeger, Aukema, & Murphy, 2017;Picklo & Murphy, 2016). In the present study, egg DHA contents were greatly increased by FLAX feeding (maximum of 106 mg/egg with the 20 g FLAX/kg diet vs. 36 mg/egg with 0 supplemental FLAX) and maximally decreased by~9% at each level of supplemental HOSO (see legend of Fig.…”
Section: Discussionsupporting
confidence: 91%
“…Reports in the literature lend support to this possibility. Two reports demonstrated that greater gains in body weight and fat mass occurred when mice were fed a high fat diet predominant in unsaturated versus saturated fats [ 32 , 33 ]. Furthermore, studies in rats [ 34 ] and humans [ 35 37 ] show that adipose tissue has a stronger correlation to the dietary profile than serum or other tissues.…”
Section: Discussionmentioning
confidence: 99%
“…It is possible that the oleic acid enriched HFD we used might have contributed to such result. High oleic acid diet was reported to suppress the hepatic elongation of essential fatty acids into arachidonic (C20:4) and docosahexaenoic (C22:6) acids impairing the hepatic secretion of triglycerides (Picklo, Idso, Seeger, Aukema, & Murphy, ). However, our results are in accordance with other reports showing that plasma triglycerides do not always change in response to HFD in mouse models of diet‐induced obesity (Biddinger et al, ; Buhman et al, ; Kirk et al, ).…”
Section: Discussionmentioning
confidence: 99%